A Study of the Use of English Among Undergraduates in Malaysia and Singapore - Pillai, Stefanie (SARE: Southeast Asian Review of English, 2017)
The English Language, transport and transplanted in Malaysia and Singapore from colonial times, has taken a linguistic shape of its own. As it began to be used by a wider range of speakers and in expanding contexts, distinct linguistic and socio-pragmatic features began to emerge as users in these countries began to adapt English to suit local tongues, norms and nuances. The increasingly wider use of English had also resulted in the birth of overlapping sub-varieties of Englishes in these countries, ranging from pidginised forms to a more acrolectal or standard form of English. The types of English used in typically ex-British colonies such as Malaysia and Singapore, are referred to, among others, as new Englishes.